A Retrospective Review of Four-Factor Prothrombin Complex Concentrate for Factor Xa Inhibitor-Related Bleedings. (April 2023) - Hitchcock, Zachary R.; Smith, Spencer D.; Le, Lamanh T.; Lees, Lauren R.; Brandt, Matthew D.
Background: The use of factor Xa inhibitors has grown in popularity; however, the risk of major bleeding events requires for the appropriate reversal agent. The recent approved agent for factor Xa inhibitor reversal, andexanet alfa, has limited clinical efficacy and safety data, and it can be a financial burden on healthcare systems due to its high cost. Four-factor prothrombin complex concentrate (4F-PCC) has been utilized off label in patients with factor Xa inhibitor-related bleedings.Objective: The aim of this study was to assess the safety and efficacy of 4F-PCC in managing factor Xa inhibitor-related bleedings. Methods: This is an observational, retrospective review of 4F-PCC usage in treating factor Xa inhibitor-related bleeds from May 2014 to December 2018 at a single health system. Efficacy was evaluated using the assessment criteria described by Sarode et al. Secondary outcomes analyzed included thromboembolic events, length of stay, mortality, and discharge disposition. Results: Fifty-nine patient charts were reviewed, and 48 patients were included in the study analysis. The administration of 4F-PCC achieved effective hemostasis in 33 patients (68%), and effective hemostasis was achieved in 12 patients (86%) who had intracranial hemorrhage and did not receive any surgical intervention. Thromboembolic events occurred in 4 patients within 30 days from 4F-PCC use. A majority of patients (85.4%) were discharged from the hospital to home or long-term care; 7 patients (14.6%) expired in the hospital. Conclusion: Efficacy was achieved in over half of the patient population in this cohort who received 4F-PCC for factor Xa inhibitor-related bleeding events.